Borderlands Coffee Project: Improving Income and Employment Opportunities among Coffee Farmers and the Displaced of Ecuador - González, Carolina; Lundy, Mark M.; Lopera, Diana Carolina; Buritica Casanova, Alexander; Rodríguez, Fernando; Sheridan, Michael; Portilla, Alex; Nobillo, Carlos; Andrade, Jairo (International Center for Tropical Agriculture, 2018)
The Bordenland Coffee Project will help 3,200 disadvantaged small farmers in 13 municipalities in the border area of Colombia and Ecuador increase their income from coffee, jobs and family resistance over a five-year period. The project will also work to influence key decision-makers in the coffee industry and among donors with action research based in the field that focuses on inclusive and sustainable business models for small coffee producers.